ANALYSIS OF SPATIAL REQUIREMENT FOR CONFINEMENT CENTRE TO SUPPORT THE NEEDS OF WOMEN WITH POSTPARTUM DEPRESSION - Abdullah, Fadzidah; Yusoff, Liyana; Abd Razak, Mohd Raziff; Yusof, Zeenat Begam; Azmin, Aida Kesuma (Journal of Architecture, Planning and Construction Management, 2021)
Women during the postpartum period are vulnerable to the problems of mental health. Having manifold emotional, behavioural, and physiological changes in their lives, postpartum women experience negative impacts on their thought, feeling, behaviours, and relationships with others. Some women need special rehabilitative spaces to reduce the negative impacts of postpartum depression. Architectural solutions with designated spatial provisions may help postpartum women to curb the negativity during their confinement stage. Hence, this research intends to analyse the spatial requirement of confinement facilities based on precedent studies that support the psychological and physical needs of postpartum depression women. This research was conducted using a qualitative approach, where precedent studies of postpartum confinement centres were analysed and compared via table research to generate spatial requirements for the effective rehabilitation of postpartum depression women. Researchers conducted interview sessions with experts to substantiate the finding of earlier comparisons. Researchers hoped that the finding of this research could outline the optimum spatial requirements for the design of a confinement centre to support the psychological and physical needs of postpartum depression women, especially those in Malaysia. The research would also serve as a platform for an effective architectural solution for reducing the negative impacts of postpartum depression among women.